2013
DOI: 10.1017/s0144686x13000949
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of ageing and later life in older people with intellectual disabilities

Abstract: The aim of this article is to explore how older people with intellectual disability (ID), who live in group accommodation, describe their lived experience in relation to ageing and later life. The article is based on a study with a phenomenological approach, grounded on the concept of life-world. Individual, qualitative interviews were conducted with  people with ID (five men, seven women), between the ages of  and  (mean = ), who lived in four different group accommodation units in southern Sweden. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
(64 reference statements)
0
16
0
4
Order By: Relevance
“…We therefore argue that discussions on occupational justice (36-37) for older people with ID need to be influenced by a life course perspective (see for example [54][55]59). This study, and others (22,38), could inform such a discussion. The life course perspective regards ageing as a dynamic process brought about by an interaction between individual, social and historical factors over time (59).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We therefore argue that discussions on occupational justice (36-37) for older people with ID need to be influenced by a life course perspective (see for example [54][55]59). This study, and others (22,38), could inform such a discussion. The life course perspective regards ageing as a dynamic process brought about by an interaction between individual, social and historical factors over time (59).…”
Section: Discussionmentioning
confidence: 72%
“…The perspectives of group home staff included in this study are, however, also important when exploring participation in this group. In an earlier study, group home residents ageing with ID accredited staff with increased importance as they and other residents became older (38). Additionally, staff perspectives, such as working methods, ambitions and values, have been shown to be important for what staff actually do (66) and thus for residents' wellbeing (13).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encore aujourd'hui, le vieillissement est perçu comme une étape de vie étroitement liée à la maladie, au sentiment de dépendance envers les autres et à la mort dans les sociétés occidentales. Bien que les PADI ne soient pas imperméables à une telle représentation, des participants à deux études (Dew, Llewellyn et Gorman, 2006;Kâhlin, Kjellberg, Nord et Hagberg, 2015) conçoivent l'avancée en âge comme une étape de vie favorable à la découverte de nouveaux intérêts et à la mise à profit de compétences acquises tout au long de leur vie. À ce sujet, plusieurs PADI ont mentionné n'avoir jamais eu autant d'occasions de réaliser des activités (p.ex., loisirs, engagement communautaire).…”
Section: Facteurs Personnelsunclassified
“…Thompson () reported that individuals may worry about continued support from FMs and access to services, but were not concerned with aging per se, which is similar to the findings of Jenkins (). In a study about the experience of aging among older adults with ID living in group accommodations, Kahlin, Kjellberg, Nord, and Hagberg () found that participants noticed changes in their physical and functional abilities, yet did not necessarily self‐identify as old. Because participants lived in a group setting, they did not express concerns about accessing services.…”
Section: Introductionmentioning
confidence: 99%